Role of Polypropylene Membranes in Enhancing Lithium Fluoride Crystallization: a Molecular Dynamics Study - Giuseppe Prenesti; Alfredo Cassano; Agostino Lauria; Alessio Caravella; Francesca Macedonio; Elena Tocci (Chemical Engineering Transactions)
The increasing demand for lithium in lithium-based batteries (LIBs) underscores the urgent need for sustainable recovery technologies, particularly for recycling exhausted batteries. Membrane-assisted crystallization (MCr) has emerged as a promising method for lithium recovery, enabling the production of high-quality crystals with minimal environmental impact. Although MCr has been widely explored across various applications, its specific role in the crystallization of lithium salts—especially lithium fluoride (LiF)—remains under-researched. This study examines the interactions between LiF solutions and polypropylene (PP) membranes during the crystallization process through molecular dynamics (MD) simulations. By comparing systems with membrane, from now on referring simply as Membrane, and without the membrane, from now on referring with the word Bulk, we highlight the membrane's pivotal role in influencing water and ion diffusion, promoting ion aggregation, and enhancing crystal formation. The results demonstrate that PP membranes slow water diffusion while facilitating ion mobility, leading to the development of more ordered and crystalline structures. Additionally, interactions with the ionic solution induce subtle morphological changes in the membrane, which influence the spatial arrangement of forming crystals. Experimental validation supports these findings, showing that PP membranes significantly improve crystal quality and structure. This work underscores the essential role of PP membranes in advancing sustainable and efficient lithium recovery technologies.